(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Hyperthyroidism is a common thyroid disorder with multiple underlying etiologies. The disease is characterized by excess of thyroid hormone production. Hyperthyroidism is associated with significant short term and long-term morbidity. Early recognition of the condition and timely instruction of appropriate therapy is crucial. Method: The data collection for hyperthyroidism included a total of 422 participants. The data was collected from July to August 2024. The sample size was calculated using Rao soft software. For data analysis Microsoft Excel 2019 was used. Statistics (frequency, cumulative frequency, percentage) was calculated. Result: Of the 422 participants 66.42 % of individuals were reported to know about treatment options of hyperthyroidism.59.28% of participants considered it life threatening. 63.57% participants considered irregular periods in women could be a symptom of hyperthyroidism. Conclusion: Study findings indicated people have understanding of hyperthyroidism but they do not consider visiting a physician for diagnosis. There is a need for early detection, prevention strategies, improved management of symptoms, proper educational campaigns.